Targeting the EGFR in cancer cells by fusion protein consisting of arazyme and third loop of TGF-alpha: an in silico study. Issue 22 (12th December 2022) - Ghadaksaz, Abdolamir; Imani Fooladi, Abbas Ali; Mahmoodzadeh Hosseini, Hamideh; Nejad Satari, Taher; Amin, Mohsen
Abstract: The anticancer effects of arazyme, a bacterial metalloprotease, have been revealed in previous studies. Because of the overexpression of epidermal growth factor receptor (EGFR) in tumor cells, targeting this receptor is one of the approaches to cancer therapy. In the present study, we designed fusion protein by using a non-mitogenic binding sequence of TGFα, arazyme, and a suitable linker. The I-TASSER and Robetta web servers were employed to predict the territory structures of the Arazyme-linker-TGFαL3, and TGFαL3-linker-Arazyme. Then, models were validated by using PROCHECK, ERRAT, ProSA, and MolProbity web servers. After docking to EGFR, Arazyme-linker-TGFαL3 showed a higher binding affinity and was selected to be optimized through 100 ns Molecular dynamic (MD) simulation. Next, the stability of ligand-bound receptor was examined utilizing MD simulation for 100 ns. Furthermore, the binding free energy calculation and free energy decomposition were carried out employing MM-PBSA and MM-GBSA methods, respectively. The root mean square deviation and fluctuation (RMSD, RMSF), the radius of gyration, H-bond, and binding free energy analysis revealed the stability of the complex during simulation time. Finally, linear and conformational epitopes of B cells, as well as MHC class I and MHC class II were predicted by using different web servers. Meanwhile, the potential B cell and T cell epitopes were identified throughout arazyme protein sequence. Collectively, this study suggests a novel chimera protein candidate prevent cancer cells potentially by inducing an immune response and inhibiting cell proliferation. Communicated by Ramaswamy H. Sarma